Reaction Mechanism for the Formation of Newly Synthesised 3-Aryl-5-tetra-O-acetyl-β-D-Glucopyranosylimidino-1,2,4-Dithiazolidines and 1-Aryl-2-Benzylimino-5-tetra-O-Acetyl-β-D-Glucopyranosyl amidinothiocarbamides, Part II - Tayade, D.T. (Asian Journal of Chemistry, 2010)
In the present work the synthesis of 3-aryl-5-tetra-O-acetyl-β-D-glucopyranosy limidino-1 ,2,4-dithiazolidines and 1-aryl-2-benzylimino-5-tetraO- acetyl-β-D-glucopyranosyl amidinothiocarbamides are described.